EPISTEMOLOGY OF ḤUḌÛRÎ IN SUHRAWARDÎ AL-MAQTÛL’S ḤIKMAT ISHRÂQIYAH - Habib, Zainal (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The epistemological thinking of á¸¥uá¸Ã»rÃ® in á¸¤ikmat al-IshrÃ¢qiyah SuhrawardÃ® has provided a new direction for the development of Islamic knowledge. In the ontological perspective, the idea of illumination provides an understanding that there is an extensive range of realities, stretching indefinitely, which ultimately leads to the understanding of essentialism. SuhrawardÃ®'s success in bringing forth this illuminative thinking entails his profound mastery of philosophy and Sufism, as well as his high intelligence in formulating Islamic thought. The only solution to the problem of developing knowledge according to SuhrawardÃ®, lies in the reality of á¸¥uá¸Ã»rÃ®Â Â (knowledge with presence), in which there are many dialogues about 'subjects who know' or 'I am performative'. In this concept, oneself knows itself through the science of á¸¥uá¸Ã»rÃ®Â (knowledge with presence), which is existentially identical to the form of 'oneself' itself.